THE IMPACT OF GAMIFICATION IN HIGH SCHOOL EDUCATION: ENGAGEMENT, LEARNING, AND YOUTH EMPOWERMENT - Campos Rodrigues, Mayara; Modesto Favacho, Kelsin; de Paula Modesto Favacho, Lúcia Helena; Lisboa Galvao do Nascimento, Jonatha; da Paz Maciel Kimura, Débora; Manoel Arrais, Daniel (Revista Gênero e Interdisciplinaridade, 2026)
Gamification, characterized by the use of game design elements in dynamic learning contexts, emerges as a pedagogical alternative to mitigate the disinterest and passivity of high school students. This article analyzes the impact of applying gamified strategies in the teaching-learning process at this stage of Basic Education. The methodology adopted consisted of a qualitative literature review, analyzing recent academic productions on the subject. The results indicate that gamification, when intentionally structured, enhances engagement, stimulates autonomy, improves the retention of complex concepts, and favors the development of socio-emotional skills. It is concluded that the insertion of game mechanics acts as a catalyst for youth protagonism, requiring, however, continuous teacher training and rigorous pedagogical planning so that technology does not overshadow learning objectives.